RACE AND EVERYDAY DISCRIMINATION ON MORTALITY RISK IN THE HEALTH AND RETIREMENT STUDY. (11th November 2018) - Farmer, H; Wray, L; Thomas, J
Abstract: Discrimination is a potent source of stress for racial minorities, and is associated with a wide range of negative health outcomes, spanning both mental and physical health. Few studies have examined the relationships linking race and discrimination to mortality in later life, leaving a major gap in the literature. Therefore, this study had three overarching aims: to examine the relationship between everyday discrimination [ED] and risk of all-cause mortality; to determine the role ED played in the relationship between race and mortality; and to investigate whether race moderated the link between ED and mortality. The sample, drawn from the nationally representative Health and Retirement Study, consisted of 13, 993 noninstitutionalized non-Hispanic Black and White adults ages 51+ living in the United States. Cox proportional hazards models were utilized to examine the aims, controlling for age, gender, and years of education. Results indicated that race (HR = 1.22, p < .05) and ED (HR = 1.19, p < .001), were significantly associated with increased risk of all-cause mortality; that ED reduced the relationship between race and mortality to non-significance; and that race did not significantly moderate the association between ED and mortality. The results from this work provide a deeper understanding of the way that racial inequalities in mortality are created. These findings contribute to a growing body of evidence on the role that discrimination plays in shaping the life chances, resources, and health of people, and in particular, minority members, who are continuously exposed to unfair treatment in their everyday lives.